Transitivity Structures and Ecological Ideology in the Awig-Awig of Desa Adat Denpasar: An Ecolinguistic and Systemic Functional Linguistics Approach - I Putu Permana Mahardika (e-Journal of Linguistics, 2026)
This study explores the ecological values embedded in the awig-awig of Desa Adat Denpasar by combining insights from ecolinguistics, Systemic Functional Linguistics (SFL), and Arne Naess’s ecosophy. The analysis focuses on how the transitivity system encodes the community’s ecological worldview through choices of process types, participant roles, and circumstantial elements. Using a qualitative phenomenological approach, several clauses from the awig-awig are examined to reveal how linguistic patterns represent obligations related to environmental care. The findings show that material processes foreground concrete ecological duties, such as maintaining vegetation and performing ritual actions in agricultural or sacred spaces. Behavioral processes highlight embodied ethical practices that frame ritual discipline as part of ecological harmony, while existential processes affirm the presence of ecological spaces like the telajakan as entities that must be preserved. These linguistic patterns indicate that the awig-awig operates not only as a regulatory text but as a cultural medium through which ecological ethics are shaped and transmitted. The study concludes that the integration of ecolinguistics, SFL, and ecosophy offers a productive framework for understanding how customary discourse sustains ecological awareness and relational ethics within Balinese communities.